European economic outlook: general report presented at the AIECE meeting in Paris, May 9 - 11, 2001 - Klaus-Jürgen Gern; Christophe Kamps; Joachim Scheide (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2001)
In the spring 2001, the world economy is in a delicate situation. The vigorous growth momentum that prevailed in the recovery in 1999 and into 2000 is clearly gone. In the second half of 2000, global growth decelerated rapidly. In contrast to the last downturn of the world economy in 1997/98, the deceleration originated in the industrial countries, where growth rates were more or less cut in half compared to the first half of the year and the OECD leading indicator declined rapidly (Figure 1.1). Major factors behind the slowdown were lagged effects of monetary tightening and the pronounced and sustained rise in oil prices. It has to be noted, however, that the loss of momentum was substantially larger than expected by most forecasters, including the AIECE institutes in fall of last year, although oil prices behaved largely as expected. The deceleration of activity was particularly pronounced in the IT sector, and the substantial weakening of demand for electronics equipment and IT consumer goods went in tandem with a dramatic decline in the price of tech stocks on a global scale. Indications that the global economy is at the brink of recession are, however, not conclusive. In most countries, business climate and consumer confidence indicators are still at relatively high levels despite the fact that they have fallen over recent months. This is true even in the United States, where the deterioration of indicators has been most pronounced, at least as consumer confidence is concerned
Keywords: 330; Konjunktur; Konjunkturprognose; EU-Staaten; Europa